The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1073/pnas.0409825102
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-electron tomography of vaccinia virus

Abstract: The combination of cryo-microscopy and electron tomographic reconstruction has allowed us to determine the structure of one of the more complex viruses, intracellular mature vaccinia virus, at a resolution of 4 -6 nm. The tomographic reconstruction allows us to dissect the different structural components of the viral particle, avoiding projection artifacts derived from previous microscopic observations. A surface-rendering representation revealed brickshaped viral particles with slightly rounded edges and dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
150
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 41 publications
12
150
1
1
Order By: Relevance
“…Recently, the presence of a single outer membrane bilayer was confirmed by freeze fracture (17) and was consistent with cryoelectron tomography (6), although the latter study suggested an additional membrane around the core. The fusion of the intracellular mature virion membrane with the plasma membrane was demonstrated by electron microscopy (2, 4) and supported by evidence for incorporation of viral membrane proteins in the plasma membrane (22) and lipid mixing studies (10).…”
mentioning
confidence: 53%
“…Recently, the presence of a single outer membrane bilayer was confirmed by freeze fracture (17) and was consistent with cryoelectron tomography (6), although the latter study suggested an additional membrane around the core. The fusion of the intracellular mature virion membrane with the plasma membrane was demonstrated by electron microscopy (2, 4) and supported by evidence for incorporation of viral membrane proteins in the plasma membrane (22) and lipid mixing studies (10).…”
mentioning
confidence: 53%
“…The virion structure is of interest not only in the context of virus assembly but also in light of the possibility that pleiomorphic variations may correlate with infectivity and/or pathogenicity. As a step toward addressing these questions, we have used cryoelectron tomography, a technique capable of rendering the 3D structures of individual macromolecular particles in their native states (19)(20)(21)(22)(23)(24)(25), to visualize influenza virions of the type A eggadapted X-31 strain (26).…”
mentioning
confidence: 99%
“…Studies on vaccinia virus in free and cell-associated states have been interpreted to provide evidence for a model in which cell attachment is required to induce decondensation of the viral DNA, and for a mechanism by which viral DNA is released into the cytoplasm by opening of the core on the side [4,34]. Electron tomographic studies on cells infected with flock house virus, a positive strand RNA virus, have been used to localize the 50 nm-sized compartments where viral RNA is synthesized and to delineate the architecture and stoichiometry of the viral replication complex [35].…”
Section: Virus-antibody Complexes and The Cellular Interfacementioning
confidence: 99%
“…However, the emergence of powerful technologies for carrying out electron tomography of viruses in isolation and in infected cells is rapidly beginning to provide novel glimpses of viral architecture in enveloped and complex viruses [4][5][6][7][8][9][10]. Here, we review some recent areas of progress and the challenges that lie ahead in this field.…”
Section: Introductionmentioning
confidence: 99%